2022
DOI: 10.1002/cnr2.1684
|View full text |Cite
|
Sign up to set email alerts
|

H2AFX might be a prognostic biomarker for hepatocellular carcinoma

Abstract: Background H2AFX can play a central role in DNA repair, replication, transcription regulation, and chromosomal stability. However, there is little research to explore the expression of H2AFX in cancers. Moreover, the correlation between the expression of H2AFX and tumor immunity, which affects the prognosis of hepatocellular carcinoma (HCC), is not clear. This article aimed to observe the correlation between H2AFX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…It was demonstrated that H2AFX sustains endothelial cells during their proliferation under hypoxia, and thereby H2AFX is important for hypoxia‐driven neovascularisation 40 . High expression of H2AFX has been ascertained in various human tumours, including melanoma, colon carcinoma, fibrosarcoma, osteosarcoma, cervical cancer, glioma, hepatocellular carcinoma and NB 33,41,42 . In this study, H2AFX expression in NB tissues was analysed by immunofluorescence, and a large percentage of positive cells was observed related with unfavourable risk factors such as MYCN amplification and metastatic stage 4.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It was demonstrated that H2AFX sustains endothelial cells during their proliferation under hypoxia, and thereby H2AFX is important for hypoxia‐driven neovascularisation 40 . High expression of H2AFX has been ascertained in various human tumours, including melanoma, colon carcinoma, fibrosarcoma, osteosarcoma, cervical cancer, glioma, hepatocellular carcinoma and NB 33,41,42 . In this study, H2AFX expression in NB tissues was analysed by immunofluorescence, and a large percentage of positive cells was observed related with unfavourable risk factors such as MYCN amplification and metastatic stage 4.…”
Section: Discussionmentioning
confidence: 89%
“…40 High expression of H2AFX has been ascertained in various human tumours, including melanoma, colon carcinoma, fibrosarcoma, osteosarcoma, cervical cancer, glioma, hepatocellular carcinoma and NB. 33,41,42 In NB, approximately 15% of localised tumours and 48% of highrisk cases carry loss or imbalance of 11q23, the site including H2AFX locus. [10][11][12] However, our data indicated that increased H2AFX expression was an unfavourable NB prognostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…PAFAH1B3 is a platelet-activating factor acetyl Hydrolase (PAF-AH), which is involved in glycolysis and lipid synthesis signaling pathway of HCC progress 14 . At the same time, histone H2AFX is highly correlated with immune cell in ltration, such as B cells, TAM, and neutrophils, which might promote HCC 15 . Besides, the downregulation of ZNF296 expression is closely related to the upregulation of MPDZ and ALDH6A1, which might suppress the progression of HCC (Figure S1E) 16,17 .…”
Section: Immune Analysis Of Different Clusters Of Immune Response For...mentioning
confidence: 99%